Impact of an educational intervention for district nurses about preparedness to encounter women exposed to intimate partner violence. Issue 2 (18th September 2017) - Sundborg, Eva; Törnkvist, Lena; Wändell, Per; Saleh‐Stattin, Nouha
Abstract : Aim: To evaluate the impact of an educational intervention on the preparedness of district nurses at primary healthcare centres to encounter women exposed to intimate partner violence. Methodological design: An observational quasi‐experimental study. Participants were divided into an intervention group (n = 117) and a control group (n = 204), both from the eastern part of Sweden. A group of nurses from across Sweden (the 'national group, ' n = 217) was also recruited. The Violence Against Women Health Care Provider Survey was used pre‐ and 1 year postintervention to measure the intervention's impact. This survey, which measured preparedness, included eight factors: practitioner preparedness, self‐confidence, lack of control, comfort following disclosure, professional support, practice pressures, abuse inquiry and consequences of asking.anova, the paired Wilcoxon test, the Mann–Whitney U test and the Kruskal–Wallis test were used to analyse the data. Findings: Pre‐intervention preparedness was equal in all three groups. In the intervention group, preparedness related to the factor practitioner lack of control increased (p = 0.003), but a comparison of change between the intervention and control groups showed no significant intervention effect (p = 0.069). Conclusions: The results indicate that the intervention had a low impact on district nurses' preparedness. The educational intervention must be adjusted; a main focus of changes should be the addition of continuing postintervention supervision and support.